Assessment and patient selection process for a pain management programme: a case study in specialty care. Issue 2 (May 2019) - Knight, Lucie D; Guildford, Beth J; Daly-Eichenhardt, Aisling; McCracken, Lance M
Introduction: The present study audited the process of assessing and selecting patients for a pain management programme with the aim of reviewing best practice in the light of the latest British Pain Society guidelines for pain management programmes for adults. The guidelines include defined inclusion/exclusion criteria and it was explored how they are used by clinicians providing a pain management service. Method: The records of 200 consecutive patients who attended a multidisciplinary assessment for a central London specialist Pain Management Service from September 2014 to December 2014 were audited. The proportions of patients who were offered a programme, were discharged or referred for a different service were calculated. Clinic letters were reviewed to collect information on assessment outcomes, recommendations and inclusion/exclusion criteria used. Results: About half the patients (53%) seen for assessment were offered treatment within the service, most frequently the intensive residential programme (30.5%, with an additional 11.6% offered case management first), followed by the five session outpatient programme (8.1%) and a minority was offered individual treatment (2.5%); 44.7% of the patients were discharged following the assessment. The three most frequently used reasons for exclusion were: not ready to engage with the pain management approach (35%), complex psychological or other needs needing to be prioritised (29.5%) and the patient declining a programme (19.3%). Conclusion: Reviewing the use of inclusion/exclusion criteria revealed some challenges regarding patient selection. For example, a sizable proportion of patients were still seeking pain reduction and were not open to a self-management approach when this was the recommended treatment for them. Complex patients might need other treatment approaches before they can be considered for a programme. Having a range of pain management options of varying intensities available seems helpful in meeting individual patient need.